Perception of the animal fable 'Bird of Paradise' song - Abd Rahim, Normaliza (Canadian Center of Science and Education, 2014)
This study focuses on perception towards the animal fable ‘Bird of Paradise’ song. The objectives of the study were to identify and discuss the characters and characterization from the ‘Bird of Paradise’ song. The samples of the study consist of ten volunteered subjects from a school in Malaysia. The subjects aged nine years old. The subjects were exposed to the animal fable Bird of Paradise song. The song was heard fifteen minutes a day in two weeks. After two weeks, the subjects were to identify and discuss on the character and characterization from the lyrics of the song. The discussion was a half an hour for each session. Each session consists of three to four subjects. The transcripts from the discussion were analyzed by using the discourse analysis method. The results of the study revealed that the subjects were able to discuss the two main characters and characterization from the song. The results also revealed that the subjects were able to identify the values from the song. Besides that, the study implicates teachers, students and lyricists in considering the animal fables as one of the materials in the classroom. It is hoped that further study will focus on other means of materials in the language classroom.